2014
DOI: 10.1680/geng.12.00110
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of laterally loaded drilled shaft group in mechanically stabilised earth wall

Abstract: This paper proposes a numerical model, calibrated by a full-scale field test, to investigate the behaviour of a laterally loaded shaft group built within a mechanically stabilised earth wall. The numerical modelling yielded results of the geogrid strain and the lateral earth pressure distributions. It was found that the strain was a maximum at the edge of the each shaft, and decreased rapidly with distance from the shaft. The additional lateral earth pressure induced by the shaft group is non-linear and non-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, there was a slight difference in the facing deformation and lateral earth pressure behind the piles of T1 and T8 (notpresented herein). Several studies [1][2][3][4] showed that increasing the lateral load on piles with MSE walls leads to greater deformation of the facing wall. However, the interaction between piles and reinforced soil is complex and may be affected by the pile offset distance, pile diameter, and load magnitude.…”
Section: Bridge Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a slight difference in the facing deformation and lateral earth pressure behind the piles of T1 and T8 (notpresented herein). Several studies [1][2][3][4] showed that increasing the lateral load on piles with MSE walls leads to greater deformation of the facing wall. However, the interaction between piles and reinforced soil is complex and may be affected by the pile offset distance, pile diameter, and load magnitude.…”
Section: Bridge Loadmentioning
confidence: 99%
“…Mohammed [2] conducted 18 model tests, and the results indicated that the lateral bearing capacity of the piles could be enhanced by increasing the wall height, reinforcement length, and pile offset distance and decreasing the reinforcement spacing. Huang et al [3] performed a three-dimensional (3D) finitedifference analysis; the results revealed that the minimum pile spacing for the group effect was significantly affected by the modulus of the backfill materials. Based on six model tests, Jawad et al [4] concluded that cyclic lateral loads have a significant impact on lateral pile capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The final paper in this edition, by Huang et al (2014), describes a numerical model calibrated by a full-scale field test for lateral loading of piles within a reinforced earth wall. Several conclusions are made regarding the spacing and interaction of the pile group and the relationship to the state and type of backfill.…”
mentioning
confidence: 99%